AB0794 Protein and Rna-Immunoprecipitation for the Identification of Autoantibodies in Patients Affected by Psoriatic Arthritis. (9th June 2015) - Ceribelli, A.; Isailovic, N.; Massarotti, M.; Tanaka, S.; Satoh, M.; Selmi, C.
Abstract : Background: Psoriatic arthritis (PsA) coexists with skin psoriasis (PsO) in 10-30% of patients. No serum autoantibody is consistently found in PsA, thus supporting the view of a chronic inflammatory rather than autoimmune pathogenesis. Further, the lack of serum biomarkers is responsible for delayed PsA diagnosis particularly in PsO. Objectives: To apply protein- and RNA-immunoprecipitation (IP) for the identification of new serologic markers of PsA. Methods: Sera from 29 adult consecutive patients with PsA were collected in the outpatient clinic of the Rheumatology Unit at the Humanitas Research Hospital. CASPAR criteria for PsA were used to establish the diagnosis in all cases. Sera were analyzed by immunoprecipitation (IP) of K562 (human erythroleukemia) cell extract radiolabeled with 35 S-methionin. RNA in the immunoprecipitate was extracted with phenol/chloroform/isoamyl alcohol and analyzed by silver staining. Clinical information was obtained from clinical correlations. Results: PsA cases are divided in polyarticular (n=23), mono/oligoarticular (n=4), and axial (n=2) phenotypes according to the pattern of joint and spine involvement. The female:male ratio is 2.2 and the mean age of PsA patients is 55 years (range 22-78 years). The mean duration of PsO is 10.3 years, while PsA mean duration is 6.8 years, with PsO preceding PsA in most individuals. One patient with PsO has polyarthritis and also positive Rheumatoid Factor and anti-CCP antibodies and is thus excluded from the series, while the other 29 PsA patients are consistently negative for both autoantibodies. Serum anti-nuclear antibodies are positive in 7/29 (24%) PsA and are speckled in 5 cases, 1 homogeneous and 1 nucleolar. IP analysis allowed the identification of specific bands corresponding to anti-Ago2/Su in 2 cases, anti-Ki/Sl in 2 cases and one weak anti-PM/Scl. None of these patients had clinical features suggestive for connective tissue disease in association with PsA. In 6/29 (20%) cases we were able to immunoprecipitate bands of variable molecular weight (48-180kD), but these do not correspond to known autoantibodies and no common band was detected in our subsets of PsA. RNA-IP did not show any specific autoantibody in the 29 PsA patients. One PsA patient later developed myositis, Raynaud's phenomenon and sclerodactily but no specific autoantibody was identified by protein- and RNA-IP. Conclusions: We report for the first time results of an extensive screening for new autoantibodies in PsA and identify specific bands and autoantibodies by protein-IP in our PsA patients, thus suggesting a possible autoimmune coexistance. The use of IP in a screening and follow-up setting may be useful to characterize new biomarkers for the early diagnosis of PsA in healthy subject and/or PsO patients. Disclosure of Interest: None declared